2020
DOI: 10.1111/ijcp.13794
|View full text |Cite
|
Sign up to set email alerts
|

Impaired thiol/disulphide homoeostasis in children with steroid‐sensitive nephrotic syndrome

Abstract: Background Abnormal thiol/disulphide homoeostasis (TDH) is responsible for the pathogenesis of various diseases. We aimed to examine the TDH in children with steroid‐sensitive nephrotic syndrome (SSNS). Methods A total of 131 children, 60 with SSNS and 71 healthy controls, participated in the study. Plasma total thiol (TT), native thiol (SH) and disulphide (SS) levels in the SSNS during remission and control groups were estimated using a new method developed by Erel and Neselioglu. Results Albumin, TT, SH leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…ROS triggers a transcription factor NF-κB-driven proinflammatory cytokines (e.g., TNF-α and IL-6) as well as chemokines (e.g., macrophage inflammatory protein-1), and thus causing an uncontrolled cytokine storm that promotes acute lung injury/ARDS in COVID-19-infected patients [ 22 ]. Thiols are part of the antioxidant defense systems that prevent or mitigate the damage of cellular components (e.g., proteins, lipids, and nucleic acids) by ROS in the organism [ 23 ]. Recently, Erel et al [ 13 ] investigated the thiol levels in COVID-19-infected patients and found that thiol levels were lower in COVID-19 patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…ROS triggers a transcription factor NF-κB-driven proinflammatory cytokines (e.g., TNF-α and IL-6) as well as chemokines (e.g., macrophage inflammatory protein-1), and thus causing an uncontrolled cytokine storm that promotes acute lung injury/ARDS in COVID-19-infected patients [ 22 ]. Thiols are part of the antioxidant defense systems that prevent or mitigate the damage of cellular components (e.g., proteins, lipids, and nucleic acids) by ROS in the organism [ 23 ]. Recently, Erel et al [ 13 ] investigated the thiol levels in COVID-19-infected patients and found that thiol levels were lower in COVID-19 patients compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The thiols have a high vulnerability to oxidation [45], forming SS when oxidised [48,49]. Since albumin is the main component of the plasma thiol pool, the SS/TT, SS/SH and SH/TT ratios are used to avoid the possible effect of albumin [25].…”
Section: Discussionmentioning
confidence: 99%
“…The study of thiol-disulphide homeostasis, which involves the analysis of serum total thiol (TT), native thiol (SH), and disulphide (SS) concentrations, is gaining interest in human medicine to evaluate oxidative status in different diseases [22][23][24][25]. Previous studies suggested that thiol-disulphide homeostasis can be used as a marker of oxidative stress in sheep during sarcoptic mange infection [26]; however, to the author's knowledge, no information about the evaluation of these biomarkers in gastrointestinal parasitism in sheep has been reported.…”
Section: Introductionmentioning
confidence: 99%